Pemanfaatan Secang dan Kayu Manis dalam Pembuatan Selai Lembaran (Kajian Organoleptik) - Firsta, Nissa Clara (AGROTECH : JURNAL ILMIAH TEKNOLOGI PERTANIAN, 2025)
This study aimed to evaluate panelists preferences for fruit leather products made from sappan wood (Caesalpinia sappan L.) and cinnamon (Cinnamomum burmannii) with varying concentrations of kappa carrageenan as a gelling agent. Sensory parameters including color, aroma, taste, texture, and overall liking were assessed using a hedonic test by 30 untrained panelists. A 4% concentration of kappa carrageenan resulted in the highest scores for texture and overall liking, while a 2% concentration was preferred for color. The distinct aroma of cinnamon and the natural reddish color from sappan were well accepted by the panelists. Overall, the fruit leather formulation made from sappan wood and cinnamon with the addition of 4% kappa carrageenan was the most preferred by consumers and has potential to be developed as a functional food product.